Instructional Leadership in Enhancing Teacher Professionalism and Learning Quality at Yayasan Mardi Yuana High Schools - Budiman, Bonefasius; Triatna, Cepi; Nurdin, Nurdin; Eisa Ruhullah, Mohammad (At-Tarbiyat, 2024)
Instructional leadership is a pivotal style that significantly enhances teachers professionalism and learning quality, yet it remains underutilized by school principals. This study aims to explore the experiences of school principals, teachers, and students in implementing instructional leadership to improve professionalism and learning quality. The research adopts a qualitative method with a phenomenological approach, focusing on Mardi Yuana High School in Cianjur and in Sukabumi. Sixteen participants, including two school principals, ten teachers, and four students, are involved. Data were collected through in-depth interviews, observations, and document analysis using Nvivo 12 Pro. Findings indicate that principals implement instructional leadership by setting goals, managing learning processes, and fostering a conducive climate, They adopt collaborative and participative principles, encouraging teachers to attend training sessions and conducting classroom supervision to enhance professionalism. Additionally, principals focus on improving learning quality by providing necessary training and learning facilities. Therefore, the optimization of instructional leadership practices is highly recommended to achieve better educational outcomes.